2022
DOI: 10.1186/s13104-022-05975-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of sleep patterns and depressive symptoms in medical students: a cross-sectional study

Abstract: Objective Mental health is a fundamental aspect in ensuring the stable and successful professional life of future physicians. Depressive symptoms can negatively affect the work-life-balance and efficiency at work of medical students. To date, there have been very few studies involving medical students that examine the association between single sleep characteristics and the outcome of the Beck Depression Inventory-II score. Therefore, the aim of the present study is to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
0
5
0
3
Order By: Relevance
“…Additionally, sleep disturbance is a risk factor for depression symptoms [18]. The occurrence of depression symptoms was related to lower sleep quality [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sleep disturbance is a risk factor for depression symptoms [18]. The occurrence of depression symptoms was related to lower sleep quality [11,19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, replacing periods of daily sedentary behavior with more physical activity has been associated with lessened symptoms of depression and anxiety (Kandola et al, 2021). Similarly, past investigators have suggested that high sleep quality may prevent or decrease symptoms of anxiety and depression in young adults (Dinis & Bragança, 2018;Dudo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, an increasing search for economic and emotional independence among young adults has contributed to reduced participation in positive health behaviors among people in this age group (Kim et al, 2021). Unhealthy lifestyle factors are common in people with MDD, and they may include low levels of physical activity, a higher percentage of time spent in sedentary behavior, and poor sleep quality (Ahmed et al, 2020; Dudo et al, 2022; Mathew et al, 2011; Vancampfort et al, 2017). Yet, a healthy lifestyle is important for people with depression to support and maintain their mental and physical health (Sarris et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, an Ethiopian study reported poor sleep quality in 56% of the student sample, with significantly higher odds for females, and lower odds for senior students (fourth semester) compared with third semester and sophomore students [ 32 ]. Indeed, poor sleep among college students including sex differences has been reported across the globe [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%